From Awareness to Compliance Government Social Media Communication and Citizens’ Behaviour toward NIN–SIM Registration in Nigeria - Raymond Udosen; T. Santas; J. S. Kente (PT Agung Media Publisher, 2025)
Government communication has increasingly shifted toward digital platforms, positioning social media as a strategic tool for public policy dissemination and behavioural influence. In Nigeria, the National Identification Number–SIM (NIN–SIM) registration policy relied heavily on social media to raise awareness and encourage compliance. However, empirical evidence explaining how such communication moves citizens from awareness to actual compliance remains limited. This study adopted a quantitative cross-sectional survey design. Data were collected from 371 residents of Lafia Metropolis, Nigeria, using a structured questionnaire. The instrument measured exposure to government social media messages, levels of policy awareness, perceived message effectiveness, and self-reported compliance behaviour. Data were analysed using descriptive statistics, including frequencies, percentages, mean scores, and standard deviations. Findings reveal high exposure to government social media communication, with 91% of respondents accessing NIN–SIM information online and 88% demonstrating clear policy understanding. Furthermore, 91% reported that social media messages influenced their decision to comply with the registration requirement. Despite these positive outcomes, structural challenges such as unreliable internet connectivity and high data costs (72%) and exposure to misinformation (69%) constrained communication effectiveness. The study confirms that government social media communication extends beyond awareness creation to actively shape compliance behaviour, consistent with the Technology Acceptance Model.